2021
DOI: 10.1101/2021.06.10.447991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploiting node metadata to predict interactions in large networks using graph embedding and neural networks

Abstract: Collecting network interaction data is difficult. Non-exhaustive sampling and complex hidden processes often result in an incomplete data set. Thus, identifying potentially present but unobserved interactions is crucial both in understanding the structure of large scale data, and in predicting how previously unseen elements will interact. Recent studies in network analysis have shown that accounting for metadata (such as node attributes) can improve both our understanding of how nodes interact with one another… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…In addition, recent advances show that the latent variables produced this way can be used to predict de novo interactions. Interestingly, the latent variables do not need to be produced by decomposing the network itself; in a recent contribution, Runghen et al (2021) showed that deep artificial neural networks are able to reconstruct the left and right subspaces of an RDPG, in order to predict human movement networks from individual/location metadata and opens up the possibility of using additional metadata as predictors.…”
Section: Methods Descriptionmentioning
confidence: 99%
“…In addition, recent advances show that the latent variables produced this way can be used to predict de novo interactions. Interestingly, the latent variables do not need to be produced by decomposing the network itself; in a recent contribution, Runghen et al (2021) showed that deep artificial neural networks are able to reconstruct the left and right subspaces of an RDPG, in order to predict human movement networks from individual/location metadata and opens up the possibility of using additional metadata as predictors.…”
Section: Methods Descriptionmentioning
confidence: 99%
“…Bringing a sparse graph into a continuous, dense vector space (Xu, 2021) opens up a broader variety of predictive algorithms, notably of the sort that are able to predict events as probabilities (Murphy, 2022). Furthermore, the projection of the graph itself is a representation that can be learned; Runghen et al (2021), for example, used a neural network to learn the embedding of a network in which not all interactions were known, based on the nodes' metadata. This example has many parallels in ecology (see Figure 1c), in which node metadata can be represented by phylogeny, abundance or functional traits.…”
Section: Graph Embedding Offers Promises For the Inference Of Potenti...mentioning
confidence: 99%
“…All codes used in the current study are available at . The data are provided in the electronic supplementary material [ 58 ].…”
Section: Data Accessibilitymentioning
confidence: 99%